2013
DOI: 10.1111/1365-2478.12094
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of magnetic data for scaling geology

Abstract: Interpretation of magnetic data can be carried out either in the space or frequency domain. The interpretation in the frequency domain is computationally convenient because convolution becomes multiplication. The frequency domain approach assumes that the magnetic sources distribution has a random and uncorrelated distribution. This approach is modified to include random and fractal distribution of sources on the basis of borehole data. The physical properties of the rocks exhibit scaling behaviour which can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 81 publications
(212 reference statements)
0
8
0
Order By: Relevance
“…). Bansal and Dimri () summarised the values of scaling exponent for the source distribution as 2.4 to 4.6 for 3D sources, which will be lower for 2D and 1D distribution of sources. A recent study by Salem et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…). Bansal and Dimri () summarised the values of scaling exponent for the source distribution as 2.4 to 4.6 for 3D sources, which will be lower for 2D and 1D distribution of sources. A recent study by Salem et al .…”
Section: Discussionmentioning
confidence: 99%
“…Some authors are of the opinion of assigning a fixed value of scaling exponent ß3 for a region (Fedi et al 1997). Bansal and Dimri (2014) summarised the values of scaling exponent for the source distribution as 2.4 to 4.6 for 3D sources, which will be lower for 2D and 1D distribution of sources. A recent study by Salem et al (2014) has shown the β value variation between 0 and 1.7 in the Central Red Sea region.…”
Section: Discussion a N D C O N C L U S I O N Smentioning
confidence: 99%
See 1 more Smart Citation
“…The statistical block-ensemble source is suitable for homogeneous blocks of different sizes and magnetization (i.e., gross homogeneous bodies) 85 , 106 . The white noise is suitable for uncorrelated, highly variable magnetization/density distributions 103 , 113 , whereas the scaling source is suitable for describing irregular magnetization/density distributions which have however some degrees of correlation 114 .…”
Section: Methodsmentioning
confidence: 99%
“…Thermal anomaly is a manifestation of renewable and environmentally benign green geothermal energy resources. Geothermal studies are carried out based on magnetic anomaly [1][2][3][4][5][6][7][8][9][10] . Curie point depth/Curie depth is the point depth at which the magnetic sources at a particu-lar geographic location within the Earth's crust lose their magnetism contents completely at a specific temperature known as the Curie point temperature [11] .…”
Section: Introductionmentioning
confidence: 99%